The Use of Thalidomide in Steroid Dependent Continous Erythema Nodosum Leprosum Leprosy Patient: A Case Report - Dian Pertiwi Habibie; M Yulianto Listiawan (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2016)
Background: Treatment thalidomide in erythema nodosum leprosum (ENL), can inhibits the transcription repression mediated by tumor necroting factor (TNF). Thalidomide can be used as sparing agents drug to reduce the dependency of steroid. Purpose: To report the effectiveness of thalidomide to treat ENL and of relinquish steroid dependency. Case: A 39 years old patient with leprosy borderline lepromatous type, came with complain bumps on skin accompanied with fever, occurring recurrently since 4 years ago if the steroid’s dose tappered off. He consumed steroid routinely every day for the last 4 years and if the dose was tapered to 4 mg once daily, the painful bumps reappeared often accompanied by fever. Thalidomide 50 mg twice daily and methyl prednisolone 4 mg once daily was given. The constant tapering off of methyl prednisolone done every week. After a month, the patient shown significant improvement. Discussion: Thalidomide is effective in ENL, it is regarded as first line in terms of clinical efficiency because it displays an effect on 90% of ENL patients. In this case, thalidomide was given and steroid dose was reduced slowly while observing the clinical manifestation and patient’s complain. There were no complain of recurrent ENL after discontinuation of steroid and thalidomide, no serious adverse event happened in this patient as well. Conclusion: The effectiveness of thalidomide in ENL is primarily due to its action on TNF but other mechanisms may contribute to its anti-inflammatory effect. Thalidomide is effective in the management of steroid dependent ENL patient. Key words: thalidomide, steroid dependent, methyl prednisolone, erythema nodosum leprosum